2011
DOI: 10.1038/aps.2011.140
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of mood stabilizers lithium, valproate and lamotrigine in experimental stroke models

Abstract: The mood stabilizers lithium, valproate and lamotrigine are traditionally used to treat bipolar disorder. However, accumulating evidence suggests that these drugs have broad neuroprotective properties and may therefore be promising therapeutic agents for the treatment of neurodegenerative diseases, including stroke. Lithium, valproate and lamotrigine exert protective effects in diverse experimental stroke models by acting on their respective primary targets, ie, glycogen synthase kinase-3, histone deacetylases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 132 publications
(175 reference statements)
2
24
0
Order By: Relevance
“…Some studies investigated the post-stroke mortality among patients with schizophrenia, and the results were controversial [10], [32], [33]. Some studies found that lithium, valproate and lamotrigine, all of which are mood stabilizers used to treat bipolar disorder, had broad neuroprotective properties and may therefore be promising therapeutic agents for the treatment of neurodegenerative diseases, including stroke [34], [35], [36]. However, we found that the incidence and mortality of stroke were higher among patients with bipolar disorder than among matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies investigated the post-stroke mortality among patients with schizophrenia, and the results were controversial [10], [32], [33]. Some studies found that lithium, valproate and lamotrigine, all of which are mood stabilizers used to treat bipolar disorder, had broad neuroprotective properties and may therefore be promising therapeutic agents for the treatment of neurodegenerative diseases, including stroke [34], [35], [36]. However, we found that the incidence and mortality of stroke were higher among patients with bipolar disorder than among matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence demonstrates that lithium and VPA exert beneficial effects throughout this pathophysiological process (for a review, see Chuang et al, 2009Chuang et al, , 2011Wang et al, 2011b) and hold clinical potential for its treatment.…”
Section: A Strokementioning
confidence: 99%
“…Studies have shown that VPA has protective properties in cellular and animal models of neurodegenerative diseases, including stroke. 1415 We have recently demonstrated that post-ischemic VPA treatment markedly attenuates blood-brain barrier (BBB) disruption and brain edema in a rat model of middle cerebral artery occlusion (MCAO), and this protection persists at least three days after ischemia. 16 However, the effects of VPA on later-phase recovery remain unclear.…”
Section: Introductionmentioning
confidence: 99%